Lipuševi deli Boštjanov let in Poizvedovanje za imenom kot sklepanje kroga s krepkejšo črto - Borovnik, Silvija (Jezik in slovstvo, 2013)
It is interesting to observe similarities between the latest prose text of Florjan Lipuš entitled Inquiry After a Name from 2013 and The Flight of Boštjan published ten years earlier, in 2003, as well as how the two works complement each other and how the latest one originates from all of the earlier ones, while at the same time transcending everything that was written before.
Keywords: Slovene literature; slovenska književnost; slovenska zamejska književnost; slovenska proza; roman; novel; novela; avstrijska Koroška; Carinthia; jezikovna identiteta; 21. st.